1995
DOI: 10.1113/jphysiol.1995.sp020800
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic metabotropic glutamatergic regulation of inhibitory synapses in rat cerebellar slices.

Abstract: 1. The effects of the metabotropic glutamate agonist trans-ACPD (t-ACPD) were investigated in various locations of the inhibitory network made by GABAergic interneurones in the molecular layer of rat cerebellar slices. 2. t-ACPD exerted complex effects on spontaneous IPSCs in Purkinje cells. IPSC frequency was transiently inhibited during short (< 1 min) applications, and enhanced upon washing. During prolonged exposure to t-ACPD, IPSCs became organized in high-frequency bursts interspersed with periods of dee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
1

Year Published

1996
1996
2009
2009

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(42 citation statements)
references
References 29 publications
3
38
1
Order By: Relevance
“…This is consistent with previous reports that modulation of GABAergic transmission by group II mGluRs is relatively homogeneous (reduction in transmitter release by presynaptic mechanisms) (Chu and Moenter 2005;Doi et al 2002;Llano and Marty 1995) and consistent among different systems (reviewed in Cartmell and Schoepp 2000;Schoepp 2001).…”
Section: Mechanisms For Modulation Of Gaba Release By Multiple Mglurssupporting
confidence: 82%
“…This is consistent with previous reports that modulation of GABAergic transmission by group II mGluRs is relatively homogeneous (reduction in transmitter release by presynaptic mechanisms) (Chu and Moenter 2005;Doi et al 2002;Llano and Marty 1995) and consistent among different systems (reviewed in Cartmell and Schoepp 2000;Schoepp 2001).…”
Section: Mechanisms For Modulation Of Gaba Release By Multiple Mglurssupporting
confidence: 82%
“…These authors also showed that activation of group I mGluRs leads to increased MLI spiking and subsequent enhancement of the frequency of spontaneous synaptic currents recorded from Purkinje cells (PCs), in accord with previous data obtained using a broad spectrum agonist (Llano and Marty, 1995). Interestingly, mGluR1 has been identified in MLIs at postsynaptic locations by immunogold staining (Baude et al, 1993).…”
Section: Introductionsupporting
confidence: 72%
“…DHPG induced three distinct events: (1) a transient inward current, which reflects the opening of cationic channels activated by mGluR1s in Purkinje cells (Batchelor et al, 1994;Tempia et al, 1998;Kim et al, 2003); (2) an increase of frequency of sIPSCs (Llano and Marty, 1995), likely through direct activation of mGluR1s and mGluR5s (Baude et al, 1993;Negyessy et al, 1997) on molecular layer interneurons; and (3) a marked decrease of the eIPSCs (Fig. 1 A).…”
Section: Resultsmentioning
confidence: 99%